Psychologists' experience of a malpractice complaint: Their relationship with and processes at the regulator - Hanlé Kirkcaldy; Esmé van Rensburg; Kobus du Plooy (AOSIS, 2020)
Background: Professional malpractice complaints in the South African health arena have increased over the last decade. There is a lack of research on how South African health practitioners experience professional malpractice complaints and complaint processes. Aim: This article reports on one aspect of the findings in a more extensive study relating to the complaint experience of psychology practitioners, namely how a group of psychology practitioners experienced their relationship with and the processes at the regulator during a malpractice complaint. The regulator refers to the professional registration body which manages complaints against practitioners. Setting: The study included 10 registered South African psychologists who experienced a malpractice complaint. Methods: After sampling, semi-structured interviews were conducted, audio-recorded and transcribed. The data were managed using interpretative phenomenological analysis (IPA) to elicit the personal, subjective experience of the individual participants. Findings: Two superordinate themes and related subthemes emerged from the analysis. First, relating to the experience of the complaint procedures and processes, participants experienced an extended timeframe for complaint management, a lack of communication during complaint management, legal challenges during some disciplinary proceedings and some complaints as unjustified and frivolous. Second, participants were unsure of their relationship with the regulator. Their responses denoted instances of vulnerability and inequality during proceedings. Conclusions: The findings call for closer collaboration between the registration body and practitioners during complaints management, to eliminate vexatious complaints, to streamline processes and to encourage guidance of and support for the professional.